Analysis of Teacher Pedagogical Competencies Using Digital Technology in Learning - Sakdiah, Halimatus; Unaida, Ratna; Akbar, Ali (PT FORMOSA CENDEKIA GLOBAL, 2024)
Current technological developments expect teachers to be able to integrate digital technology into the learning process to improve the effectiveness and quality of education. This study aims to analyze the use of digital technology in learning. This research method is Descriptive and Quantitative use a questionnaire as an instrument. The population of this study was professional teacher education students at Malikussaleh University who were teachers as many 400 people drawn as a random sample. The study results showed that the pedagogical competence of prospective professional teachers was in the very high category in 91.352%, as many 30.83% of respondents chose to use video media as their teaching.